The PAPSS1 gene is a modulator of response to cisplatin by regulating estrogen receptor alpha signaling activity in ovarian cancer cells - Lei Sun; Wei-Xue Ji; Yan Li; Ze-Lian Li; Can-Can Duan; Bai-rong Xia; Lan Xiao (BMC, 2023)
Abstract Background Cancer cells may develop resistance to cisplatin by various mechanisms. Yet, the exact mechanism of cisplatin in ovarian cancer remains unclear. Recent studies have shown that 3'-phospoadenosine 5'-phosphosulfate synthase 1 (PAPSS1) inhibition combined with low-dose cisplatin increases DNA damage. The aim of this study was to determine the value of targeting PAPSS1 as a cisplatin modulator in epithelial ovarian cancer (EOC). Results Increased expression of PAPSS1 was observed in both EOC cells and tissues. Also, its higher nuclear expression was distinctly associated with FIGO (The International Federation of Gynecology and Obstetrics) stage, histological subtype, metastasis, and recurrence. Down-regulation of the PAPSS1 gene increased the cisplatin sensitivity of EOC in vitro and in vivo. Expression of PAPSS1 was negatively correlated with estrogen receptor α (ERα) in EOC. Also, low nuclear PAPSS1 and high nuclear ERα expression in EOC were associated with longer overall survival and progression-free survival in all ovarian cancer and ovarian cancer patients who received platinum-based chemotherapy. PAPSS1 silencing increased the activity of ERα-signaling in EOC cells, thus sensitizing tumors to cisplatin. Conclusions These findings characterize a novel interplay between PAPSS1-mediated sulfation and ERα-signaling in EOC cisplatin resistance. PAPSS1 may be exploited as a cisplatin-sensitizing therapeutic target.